Repurposing ribosome-targeting antibiotics to overcome resistance to venetoclax in acute myeloid leukemia. (3rd March 2020) - Sharon, David; Chan, Steven M.
ABSTRACT: Venetoclax, a selective B-cell lymphoma 2 inhibitor, has shown promise in the treatment of acute myeloid leukemia. However, the development of drug resistance limits its clinical efficacy. In our study, we discovered that ribosome-targeting antibiotics can be repurposed to overcome venetoclax resistance in AML cells through activation of the integrated stress response.